Alterations in the polarization of liver M1/M2 macrophages upon long-term administration of triptorelin in rats - M.V. Rud; Y.V. Stetsuk; V.I. Shepitko; O.V. Vilkhova; L.B. Pelypenko; O.V. Voloshyna; A.G. Sydorenko; H.P. Pavlenko; N.M. Sharlai; O.V. Sych (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Liver macrophages play a pivotal role in maintaining the homeostasis of the liver and the entire body, they may be classified into three categories based on their origin. M1 macrophages, designated as classically activated macrophages, differentiate from macrophages stimulated by interferon-gamma or ligands of Toll-like receptors. M2 cells are derived from macrophages that have been stimulated by IL-4/13. Prostate cancer is the second most prevalent malignancy in men globally. Androgen deprivation therapy using gonadotropin-releasing hormone agonist remains the backbone of advanced prostate cancer treatment. The purpose of our study was to ascertain the impact of testosterone suppression on immunocompetent hepatic cells in male rats. The study employed a series of experimental periods, with the introduction of triptorelin and quercetin at varying stages. Materials and methods. The study was conducted on 35 sexually mature male rats. They were randomly allocated to two groups: the controls (n = 10) and the experimental one (n = 25). The animals in the experimental group were administered a solution of triptorelin at a dose of 0.3 mg of active ingredient per 1 kg of body weight, with the aim of modulating the central deprivation of luteinizing hormone synthesis. We used primary antibodies against CD163 and CD68. Results. In the livers of animals on day 30 of the experiment, the number of CD68+ cells were calculated to be 12.2400 ± 1.5792 per FOV at p < 0.01, which is 2.2 times higher than in the control group. The expression of CD163+ with a value of 25.04 ± 1.79 (p < 0.01) is 5.56 times higher compared to the controls. On day 90, the number of cells exhibiting CD68+ and CD163+ expression was 29.34 ± 1.86 and 25.66 ± 4.22, respectively, at p < 0.01, representing a 5.46-fold increase compared to the FOV in the control group preparations. The 180th day of observation was defined by a reduction in the expression of CD68+ as compared to the earlier examination period. Conversely, the expression of CD163+ in cells increased, representing a 40% rise compared to the previous examination period. On day 270 of the experiment, a gradual increase in the expression of cells with CD68+ (9.86 ± 1.47; p < 0.05) was demonstrated. Conclusions. The long-term administration of triptorelin causes changes in quantitative and qualitative modifications of the macrophage population. Maximum of M1 phenotype are detected at 3 and 12 months of observation. The number of M2 phenotype increases by 6 months of monitoring, with a gradual decrease by 12 months.